PERANCANGAN SYSTEM ABSENSI KARYAWAN BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE DI GANBATEA INDONESIA - Sugiartha, Rama Albin; Muhamad, Fariz; Adzhim, Muhamad Arsyil; Haryono, Wasis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2023)
Technological developments are increasingly rapid and many fields exist and need to be developed. One of them is information technology. This is a field that is closely related to technological developments. Without information technology, developments that occur will not be as advanced as this. Understanding information technology in general is a study of the design, implementation, development, support or management of computer-based information systems, especially in hardware (hardware) and software (computer software) applications. In software testing, one of the methods used is to use Prototype method. The prototype method has its own technique, one of which is a system development technique that uses a prototype to describe the system so that the client or system owner has a clear picture of the system that will be built by the development team. Prototype in Indonesian is called prototype (initial form).